2012
DOI: 10.1001/2012.jama.11274
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Fractional Flow Reserve From Anatomic CT Angiography

Abstract: ORONARY COMPUTED TOMOgraphic (CT) angiography is a noninvasive test that enables direct visualization of coronary artery disease (CAD) and correlates favorably with invasive coronary angiography (ICA) for measures of stenosis severity. 1 However, CT cannot determine the hemodynamic significance of CAD, and even among CTidentified obstructive stenoses confirmed by ICA, fewer than half are ischemia-causing. 2,3 These findings underscore an unreliable relationship of stenosis severity to ischemia and have raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
562
1
27

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,040 publications
(600 citation statements)
references
References 30 publications
10
562
1
27
Order By: Relevance
“…To further expand the use of physiological‐guided percutaneous coronary intervention, coronary computed tomography angiography– and invasive coronary angiography–based computation methods were developed for less‐invasive FFR approximation 4, 5, 6, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…To further expand the use of physiological‐guided percutaneous coronary intervention, coronary computed tomography angiography– and invasive coronary angiography–based computation methods were developed for less‐invasive FFR approximation 4, 5, 6, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Based on these techniques, noninvasive fractional flow reserve (FFR) can be computed 3, 4, 5, 6. In studies including patients with known or suspected stable CAD and blinded comparison to FFR, coronary CTA‐derived FFR (FFR CT ) has shown high diagnostic performance 4, 5, 6. Recently, it was demonstrated in stable patients referred to ICA that initial FFR CT assessment reduced the downstream use of ICA procedures, the rate of ICA showing no obstructive CAD, and overall costs 7.…”
Section: Introductionmentioning
confidence: 99%
“…4,21 This expands the usefulness of coronary CTA by combining anatomic and functional assessment and raises the potential of coronary CTA to help define those patients that may derive benefit from invasive angiography and possible revascularization. Furthermore, FFR CT analysis provides functional information at all locations in the coronary tree adding a richness of information which may be useful in clinical decision making.…”
Section: Discussionmentioning
confidence: 97%
“…The diagnostic accuracy of FFR CT for the detection of lesion-specific ischemia has recently been compared with that of coronary CTA alone using invasive FFR as the reference standard. 4 The DISCOVER-FLOW trial demonstrated improved diagnostic accuracy of FFR CT vs coronary CTA stenosis at a per-vessel level when compared to invasive FFR. 5 The Determination of Fractional Flow Reserve by Anatomic Computed Tomographic Angiography (DeFACTO) study also demonstrated improved diagnostic accuracy and improved discriminatory power of FFR CT compared to coronary CTA alone for the diagnosis of ischemia in stable patients with CAD at a lesion-specific level, including those with intermediate stenosis.…”
Section: Introductionmentioning
confidence: 97%